Titanium Alloys - Advances in Properties Control 2013
DOI: 10.5772/54626
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Microstructural Evolution of Titanium During Diffusive Saturation by Interstitial Elements

Abstract: coefficient of nitrogen or oxygen in titanium Panasyuk, Metin, Kofstad, . This is why investigations experimental and theoretical aimed at elucidating the kinetic regularities and peculiarities of the distribution of interstitial elements in a surface layer, which determines the changes of its physicomechanical characteristics, are urgent.Diffusive processes determine changes of properties of surface layers of the structural materials in many cases, for example, in the process of their thermochemical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…It can be observed that the decreasing of gas pressure and the increasing of DC bias voltage plays an important role in the formation of compound layer, e.g. the concentration of TiN fine precipitation increased from 1.71% to 8.71% during the process at lower pressure and DC bias voltage of -600 V. The most important factor that determines the formation of TiN as the compound layer is the effectiveness of diffusion process onto the surface of titanium specimen that occurs in the nitriding process [3].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be observed that the decreasing of gas pressure and the increasing of DC bias voltage plays an important role in the formation of compound layer, e.g. the concentration of TiN fine precipitation increased from 1.71% to 8.71% during the process at lower pressure and DC bias voltage of -600 V. The most important factor that determines the formation of TiN as the compound layer is the effectiveness of diffusion process onto the surface of titanium specimen that occurs in the nitriding process [3].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted here, that the use of low-pressure discharge of the nitriding process can enhance the formation of TiN due to the high density of plasma ions in the low gas pressure. If nitrogen with high concentration diffused rapidly to the surface of the material, saturation will be more quickly formed, so that there will be a bond between the titanium atoms with the nitrogen atoms to form a compound layer of TiN [3,20]. In addition, the use of high DC bias voltage will also greatly affect the effectiveness of diffusion processes because the accelerated ions and fast neutral have high energy at higher voltage [17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations